PENGEMBANGAN MEDIA PEMBELAJARAN BILIK BAHASA MATERI UNSUR KALIMAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II SDN KEDIREN BLORA - Putri Handarista; Fajriyah, Khusnul; Mudzanatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The background underlying this research is the existence of problems that exist in the classroom based on preliminary observations made by researchers, namely students do not understand the material presented and cause student learning outcomes to be less than optimal due to the limited learning media used by teachers during the teaching and learning process, especially in Indonesian language subjects. The objectives to be achieved in this study 1) Can develop language booth learning media related to sentence element material, 2) Can determine the feasibility of developing language booth learning media related to sentence element material to improve learning outcomes of grade II students, 3) Can determine the effectiveness of developing language booth learning media related to sentence element material to improve learning outcomes of grade II students. This type of research is Research and Development (R&D) proposed by Borg and Gall using a development procedure of up to 10 stages, but the researcher modified the development steps into 5 stages, namely 1) Research and Information Collecting, 2) Planning, 3) Develop Preliminary of Product, 4) Preliminary Field Testing, and 5) Main Product Revision. The results of research on the development of language booth learning media with validity results obtained based on teacher and student response questionnaires with a score of 100% with the category “Very Feasible”. While the effectiveness results were obtained from N-gain testing from the average pretest score of 65.29 and the averageposttest score of 90 and obtained a percentage of 71% with a classification of “Moderate”. It is concluded that through the development of learning media “Language Booth” the material of sentence elements is effective to improve the learning outcomes of grade II students in Indonesian language subjects.